The function of recycled lithic items at late Lower Paleolithic Qesem Cave, Israel: An overview of the use-wear data. (10th March 2015) - Lemorini, Cristina; Venditti, Flavia; Assaf, Ella; Parush, Yoni; Barkai, Ran; Gopher, Avi
Abstract: The study of lithic recycling in Paleolithic cultures throughout the Old World is increasingly becoming a topic of interest for many scholars. Technological analyses, refitting, and spatial analyses are disclosing the "recycling behavior" of many contexts, especially those of Lower and Middle Paleolithic sites. Still lacking, however, is a functional approach to the subject, which would certainly add new pieces to this intriguing jigsaw puzzle. Use-wear analysis, one of the most powerful methods to reach functional interpretations in lithic finds, can greatly improve our understanding of Paleolithic recycling behavior. Even in those cases where post-depositional alterations affected lithic items, use-wear analyses may produce important data despite the decrease in detail or less than optimal conditions of preservation. At the late Lower Paleolithic site of Qesem Cave, the high degree of conservation and preservation of the lithic tools maximizes the inference potential of this method. In this article, functional data are summarized following a study of a large sample of Amudian parent flakes (flakes from which were produced cores on flakes, termed COF-FFs) as well as recycled products (blanks produced from COF-FFs). Confirming the inference potential of use-wear analyses, this data allows for the delineation of functional peculiarities of the studied items, which, despite first impression, are anything but expedient. Moreover, the current use-wear analysis expands the scenario outlined by the technological study of the lithic recycling phenomenon at Qesem Cave, confirming its own role in the complex techno-functional system practiced by the hominins of Qesem Cave.